Obsolescência da função do intelectual na modernidade - Santos, Roberval de Jesus Leone dos (Estudos Avançados, 2002)
In this paper is discussed the evolution of the function of the intellectual in the capitalist societies and are showed the necessary and sufficient conditions for the function performance. Starting from the non attendance of some of those conditions, the author shows the tend of a future in which this essentially human function will stop being indispensable.